Tattoo traditions of Asia : ancient and contemporary expressions of identity - Krutak, Lars F. (Honolulu : University of Hawaʻi Press, 2024)
"For millennia, tattoos have documented the history of humanity one painful mark at a time. They form a visual language on the skin, expressing an individual's desires and fears as well as cultural values, family ties, and spiritual beliefs on the surfaces of the body. The Indigenous peoples of Asia have created some of the world's oldest and most distinctive tattoos, but their many contributions to body art and practice have been largely overlooked. Tattoo Traditions of Asia is the first single volume dedicated to the anthropological study of an ancient cultural practice and artform that spans many countries and societies, ancestral lands, and contemporary communities across the continent and its islands. This richly illustrated survey combines the author's twenty years of fieldwork, interviewing hundreds of Indigenous tattoo bearers and contemporary tattoo practitioners, with painstaking research conducted in obscure archives throughout the region and elsewhere to break new ground on one of the least-understood mediums of Indigenous Asian expressive culture-a vital tradition to be celebrated, an inspirational story told in skin and ink"--
Frontmatter -- Dedication -- Contents -- Preface -- Acknowledgments -- Note on Terms -- Introduction -- 1. Tattoos of Japan: Many Islands, Many Tales -- 2. Tattoos of Taiwan and Hainan: To Honor the Ancestors -- 3. Tattoos of the Philippines: Defining Marks of Culture -- 4. Tattoos of Indonesia: Spirits, Souls, Taboo, and Tattoo -- 5. Tattoos of Mainland Southeast Asia: Magical Mysteries in Ink -- 6. Magical Mysteries in Ink: Marks for the Afterlife -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 05, 2024).
JSTOR
Keywords: Tattooing -- Asia -- History; Indigenous art -- Asia; Indigenous peoples -- Asia -- Social life and customs; Tatouage -- Asie -- Histoire; Art autochtone -- Asie; ART / Body Art & Tattooing; Indigenous art; Indigenous peoples -- Social life and customs; Tattooing; Asia; History